If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5h + 4)(3h + 6) = 0 Reorder the terms: (4 + 5h)(3h + 6) = 0 Reorder the terms: (4 + 5h)(6 + 3h) = 0 Multiply (4 + 5h) * (6 + 3h) (4(6 + 3h) + 5h * (6 + 3h)) = 0 ((6 * 4 + 3h * 4) + 5h * (6 + 3h)) = 0 ((24 + 12h) + 5h * (6 + 3h)) = 0 (24 + 12h + (6 * 5h + 3h * 5h)) = 0 (24 + 12h + (30h + 15h2)) = 0 Combine like terms: 12h + 30h = 42h (24 + 42h + 15h2) = 0 Solving 24 + 42h + 15h2 = 0 Solving for variable 'h'. Factor out the Greatest Common Factor (GCF), '3'. 3(8 + 14h + 5h2) = 0 Factor a trinomial. 3((2 + h)(4 + 5h)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(2 + h)' equal to zero and attempt to solve: Simplifying 2 + h = 0 Solving 2 + h = 0 Move all terms containing h to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + h = 0 + -2 Combine like terms: 2 + -2 = 0 0 + h = 0 + -2 h = 0 + -2 Combine like terms: 0 + -2 = -2 h = -2 Simplifying h = -2Subproblem 2
Set the factor '(4 + 5h)' equal to zero and attempt to solve: Simplifying 4 + 5h = 0 Solving 4 + 5h = 0 Move all terms containing h to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5h = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5h = 0 + -4 5h = 0 + -4 Combine like terms: 0 + -4 = -4 5h = -4 Divide each side by '5'. h = -0.8 Simplifying h = -0.8Solution
h = {-2, -0.8}
| 3.9=r^2 | | 4c^2+4c-1=0 | | (9x+1)+(11x-23)=180 | | -5(x+3)-14=10+1 | | 3(x+30)=5x-30 | | 18=10-8(x-2) | | 3a^2+2b-6a+ab= | | 2m+5=10m | | (13y+5)-(2y+2)= | | 3x^2+12x+9=30 | | 0.09xX=95.63 | | -11+21+(-20)+(-21)= | | 2msq+5=10m | | -10u=16-11u | | 7=logx/10^(-12) | | 9f=10f-8 | | 200x+600y=4400 | | -7x-143=3x+107 | | 2/5a=3/20 | | -5r+9=-6+10r | | x-9=-9x | | -10-h=h+8h+10 | | -8c=-10c-8 | | 3r+7x+1=2(5x+1) | | 2+8q=8+9q | | 6x(x+1)=20-x | | 16/8=x/12 | | R-12=28 | | 0.876n=0.625n+4 | | 8-4d=-2d-10 | | 8=log(x/10^-12) | | R-12=12 |